Importance-performance analysis of service quality dimensions for the Bangladeshi hotel industry - Rahman, Mahbubar; Islam, Rafikul (Inderscience Enterprises Ltd., 2018)
In global competitive markets, hoteliers are looking to satisfy guests for repeat customers. Achieving satisfied guests is not an easy task. This study evaluates the service quality of Bangladeshi hotels using gap analysis, SERVQUAL and importance-performance analysis (IPA). The results showed that hotel guests’ satisfaction regarding service attributes are lower than the importance assigned to the measurement attributes. The widest gap was found in staff response and additional amenities, especially the commitment of hotel staff towards their guests. Also, the IPA grid showed that eight services attributes fell into the ‘concentrate here’ quadrant. This means that hotel management should take immediate action on these attributes for the betterment of the industry.